2015
DOI: 10.1590/0074-02760150300
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural alterations are independent of sickness behaviour in chronic experimental Chagas disease

Abstract: The existence of the nervous form of Chagas disease is a matter of discussion since Carlos Chagas described neurological disorders, learning and behavioural alterations in Trypanosoma cruzi-infected individuals. In most patients, the clinical manifestations of the acute phase, including neurological abnormalities, resolve spontaneously without apparent consequence in the chronic phase of infection. However, chronic Chagas disease patients have behavioural changes such as psychomotor alterations, attention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…To approach our questions, C57BL/6 mice were infected with low inoculum of blood trypomastigotes of the Colombian type I T . cruzi strain, which allowed immune response to control parasite, host survival and development of the chronic phase of infection [ 18 , 22 ]. Further, in comparison with age-matched non-infected controls, chronically infected mice did not display neuromuscular disorders assessed by grip strength meter test, and, therefore, suitable as an experimental model to address our issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To approach our questions, C57BL/6 mice were infected with low inoculum of blood trypomastigotes of the Colombian type I T . cruzi strain, which allowed immune response to control parasite, host survival and development of the chronic phase of infection [ 18 , 22 ]. Further, in comparison with age-matched non-infected controls, chronically infected mice did not display neuromuscular disorders assessed by grip strength meter test, and, therefore, suitable as an experimental model to address our issues.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have described that in chronically T . cruzi -infected C57BL/6 mice depressive-like behavior, anxiety and motor coordination disorder occur independently of sickness behavior and neuromuscular disorder [ 17 , 18 ]. The present study was carried out to evaluate the presence of memory impairment in chronically T .…”
Section: Introductionmentioning
confidence: 99%
“…The acute phase lasts for the first few weeks or months of infection; it can be asymptomatic or include fever, fatigue, and local swelling (called chagoma). In the chronic phase, patients usually have cardiac abnormalities, as well as digestive, neurological, or mixed alterations; recently, it has been shown that they also have behavioral changes, such as psychomotor alterations, attention and memory deficits, as well as depression [52]. Chemotherapy involves the use of two drugs: nifurtimox and benznidazole.…”
Section: Mexican Medicinal Plants Againstmentioning
confidence: 99%
“…Nevertheless, in some cases, this indeterminate form is followed by symptomatic forms of the chronic phase, characterized by decrease in parasitemia and by cardiac, digestive or neurological manifestations 1,11 . Moreover, some preclinical and clinical studies reported that, in the chronic phase of CD, there are behavioral changes and the occurrence of psychiatric comorbidities such as anxiety and depression, conditions that, in principle, cannot solely be explained by the psychological status of the patient [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%